Decomposing a prior-CT-based cone-beam CT projection correction algorithm into scatter and beam hardening components. (July 2017) - Zöllner, Christoph; Rit, Simon; Kurz, Christopher; Vilches-Freixas, Gloria; Kamp, Florian; Dedes, George; Belka, Claus; Parodi, Katia; Landry, Guillaume
Abstract: A scatter correction algorithm (SCA) for cone beam CT (CBCT) projections, making use of prior information obtained by deformable image registration of CT to CBCT, has recently been proposed and tested for particle therapy dose calculation. The SCA relies on subtraction of digitally reconstructed radiographs (DRR) from scaled measured projections and smoothing operations, followed by a subtraction correction and reconstruction. In this note, we compared the SCA's correction to one based on a Monte Carlo simulation of the scatter, and a separate beam hardening correction. Agreement better than 3% between the two approaches was obtained when comparing corrected log-transformed projections.